Conflicts between humans and wild animals in and surrounding protected area (Bahia, Brazil): an ethnozoological approach - Santos, Jade Silva dos; Teixeira, Joanison Vicente dos Santos; Guanaes, Deyna Hulda Arêas; Rocha, Wesley Duarte da; Schiavetti, Alexandre (Ethnobiology and Conservation, 2020)
Conflicts among humans and wildlife have been considered as a huge obstacle to management and conservation of fauna, and also lead to negative impacts for local populations. For this reason, from an ethnozoological perspective, the present work aimed to identify and analyze conflicts among farmers and the wild fauna in four communities of the Costa de Itacaré-Serra Grande Environmental Protection Area, Bahia - Brazil. In addition to diagnose the control measures used. The choice of participants was performed using the snow ball technique, and data collection was realized from semi-structured interviews, complemented by free listing techniques, nonspecific prompting and reading back. Thirty-eight farmers were interviewed, reporting 45 species of wild animals, among which 23 were mammals, 17 birds and 05 reptiles. Conflicts were classified in five categories, in which animal-cultivation and animal-livestock interactions presented the highest number of reported species. Farmers applied different control measures, including defensive methods, which are the most used in the communities, offensive methods and superstitious rituals. Positive interactions were also identified, in which some species are considered as charismatic or recognized by its ecological role. Conflicts with wild fauna are recurrent in these communities, thus, it is necessary to guarantee social participation in the construction of effective strategies of conflict mitigation and fauna conservation.